The satisfaction with sex life across the adult life span - Félix Neto (2013)
Three separate issues concerning the relation between age and satisfaction with sex life are addressed in this article. The first issue was concerned with the age generalizability of the factor structure produced by responses to the Satisfaction with Sex Life Scale (SWSLS). The second issue was to examine whether there were differences in the satisfaction with sex life according to certain background characteristics, namely age. Finally, the relationship between scores on the SWSLS with those on other relational constructs was explored. Data collection involved completion of a questionnaire. The sample consisted of 1,144 participants. The mean ages of the sample were 38.99 years in (SD = 16.91); ages ranged from 20 to 80. The data indicated that the factor structure of responses to the SWSLS were highly similar through adult life. Religious involvement, marital status, and love status influenced satisfaction with sex life. Expected correlations with measures of other relationship constructs were found. The strongest predictor of satisfaction with sex live across the adult life span was love satisfaction. Suggestions concerning the use of the SWSLS for research and clinical purposes are offered. (c) 2012 Springer Science+Business Media Dordrecht.